Eosinophilic Esophagitis: Review and Update - Gomez Torrijos, Elisa; Gonzalez-Mendiola, Rosario; Alvarado, Manuela; Avila, Robledo; Prieto-Garcia, Alicia; Valbuena, Teresa; Borja, Jesus; Infante, Sonsoles; Lopez, M. Pilar; Marchan, Eva; Prieto, Patricia; Moro, Mar; et al. (Frontiers in Medicine, 2018)
Background Eosinophilic esophagitis (EoE) was first described in the 1990s, showing an increasing incidence and prevalence since then, being the leading cause of food impaction and the major cause of dysphagia. Probably, in a few years, EoE may no longer be considered a rare disease. Methods This article discusses new aspects of the pathogenesis, symptoms, diagnosis, and treatment of EoE according to the last published guidelines. Results The epidemiological studies indicate a multifactorial origin for EoE, where environmental and genetic factors take part. EoE affects both children and adults and it is frequently associated with atopic disease and IgE-mediated food allergies. In patients undergoing oral immunotherapy for desensitization from IgE-mediated food allergy the risk of developing EoE is 2.72%. Barrier dysfunction and T-helper 2 inflammation is considered to be pathogenetically important factors. There are different patterns of clinical presentation varying with age and can be masked by adaptation habits. Besides, symptoms do not usually correlate with histologic disease activity. The diagnostic criteria for EoE has evolved but mainly requires symptoms of esophageal dysfunction with histologic evidence of a peak value of at least 15 eosinophils per high-power field. Endoscopies have to be repeated in order to diagnose, monitor, and treat EoE. Treatment of EoE can be started either by drugs (PPIs and topical corticosteroids) or elimination diets. The multistage step-up elimination diet management approach of EoE is promising. Endoscopic dilation is used for patients with severe dysphagia/food impaction with inadequate response to anti-inflammatory treatment. Conclusions Research in recent years has contributed to a better understanding of EoE's pathogenesis, genetic background, natural history, allergy workup, standardization in assessment of disease activity, evaluation of minimally invasive diagnostic tools, and new therapeutic approaches. However, several unmet needs are to be solved urgently, as finding a non-invasive disease-monitoring methods and biomarkers for routine practice, the development or new therapies, novel food allergy testing to detect triggering foods, drug and doses required for initial therapy and safety issues with long-term maintenance therapy, amongst others. Besides, multidisciplinary management units of EoE, involving gastroenterologists, pediatricians, allergists, pathologists, dietitians and ENT specialists are needed.